Ventricular arrhythmias and implantable cardioverter-defibrillator therapy in women: a propensity score-matched analysis. (19th May 2022) - Maglia, G; Giammaria, M; Zanotto, G; D'onofrio, A; Della Bella, P; Marini, M; Rovaris, G; Iacopino, S; Calvi, V; Pisano', EC; Caravati, F; Balestri, G; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The implantable cardioverter-defibrillator (ICD) is an established therapy for the prevention of sudden cardiac death in selected patients. Although current guidelines apply to both women and men, there is a growing awareness that the incidence of cardiac arrhythmias and device interventions is influenced by sex. Purpose: To investigate sex-specific risk of sustained ventricular arrhythmias (SVAs) and device therapies, using remote monitoring data from ICDs and cardiac resynchronization therapy defibrillators (CRT-Ds). Methods: Study endpoints were time to the first appropriate SVA, time to the first appropriate device therapy for SVA, and time to the first ICD shock. Appropriateness of device-detected SVAs was adjudicated by three expert electrophysiologists. Results were compared between women and a 1:1 propensity score (PS)-matched subgroup of men. Results: In a cohort of 2, 532 patients with an ICD or CRT-D (median age, 70 years), 488 patients (19.3%) were women. As compared to men, women more frequently had a CRT-D (51% vs. 40%, p<0.001), and nonischemic cardiomyopathy (65% vs. 45%, p<0.001). After a median follow-up of 2.1 years, SVAs occurred in 123 women (25.2%) and in 174 of the 488 PS-matched men (35.6%) with an adjusted hazard ratio (HR) of 0.65 (95% confidence interval [CI], 0.51-0.81; p<0.001). Women also showed a reduced risk of any device therapy (HR, 0.59; CI, 0.45-0.76; p<0.001) and shocks (HR, 0.66; CI, 0.47-0.94, p=0.021). Differences in sex-specific SVA risk profile were not confirmed in CRT-D patients (HR, 0.78; CI, 0.55-1.09; p=0.14) and in those with an ejection fraction <30% (HR, 0.80; CI, 0.52-1.23; p=0.31). Conclusion: In our analysis of remote monitoring data, women exhibited a lower SVA risk profile than PS-matched men in the subgroup of patients with an ICD or/and ejection fraction ≥30%.